(untitled) (Research, Society and Development, 2021)
Respiratory failure is, from the clinical presentations of COVID-19, the one that demands greater prominence, but kidney involvement is described as a relevant clinical picture. Acute Kidney Injury (AKI) is defined as the abrupt loss of kidney function and has been associated with high mortality rates and a poor renal prognosis in critically ill patients with the infection. Objective: Analyze the incidence of acute renal failure secondary to COVID-19 in an Intensive Care Unit (ICU). Method: Qualitative, quantitative and retrospective documentary research in medical records of patients from an ICU in Southwest Goiás with a positive diagnosis for COVID-19, interned during September 1, 2020 to April 30, 2021. For AKI stratification, the criteria of AKI were considered. KDIGO. Results: From the 212 patients, 60 progressed to AKI, with a predominance of 80% in stage 3. The average age was 62.6 and the highest incidence in males was 51.67%. The average hospital stay was 11.6 days. The most prevalent comorbidities were: Hypertension: 53.33% and Diabetes Melitus: 31.67%. Regarding nephrotoxic drugs, 78.33% are vasodilators. The clinical complications: 88.33% required invasive ventilatory support and, 80% needed hemodialysis, whereas 93.33% progressed to death. Conclusion: It is concluded that there was a high incidence of AKI, with a strong influence on mortality, mainly associated with risk factors such as older age, comorbidities and clinical management such as ventilatory support, need for hemodialysis and the use of vasoactive drugs.